PENGARUH PENDEKATAN SAINTIFIK DENGAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN FIQIH KELAS VII MTs RAHMAT SAID BONGKOT - Siti Umdlotul Khoiroh; Mohammad Saat Ibnu Waqfin; Hidayatur Rohmah (Universitas KH. A. Wahab Hasbullah, 2020)
This research is motivated by a phenomenon that occurs in students regarding conventional learning models that make students less active and student learning outcomes are low. In this article discuss the problem of learning models and learning outcomes. This study aims to determine the effect of the Discovery Learning model on Fiqh learning to improve student learning outcomes. In this study using the True Experimental Design method and implemented at MTs Rahmat Said Bongkot PeteronganJombang. The sampling technique uses Simple Random Sampling. based on the results of the study obtained data as follows: 1) the average results of the implementation of learning by 85% with very good criteria; 2) the results of student responses amounted to 81.5% with very good criteria; 3) the average results of the test description of student learning outcomes by 75% with high criteria, and the results of the hypothesis test for the t-test two free samples with the acquisition of a significance value <0.05 then H0 is rejected and H1 is accepted. So it can be interpreted that the Discovery Learning learning model has an effect in improving student learning outcomes.